La Société du spectacle - Debord, Guy 1931-1994 (Paris Gallimard, 1992)
The spectacle is a central notion in the Situationist theory, developed by Guy Debord in 'La société du spectacle'. In the general sense, the spectacle refers to "the autocratic reign of the market economy which had acceded to an irresponsible sovereignty, and the totality of new techniques of government which accompanied this reign." It also exists in a more limited sense, where spectacle means the mass media, which are "its most glaring superficial manifestation." Debord said that the society of the spectacle came to existence in the late 1920s.The critique of the spectacle is a development and application of Karl Marx's concept of fetishism of commodities, reification and alienation, and the way it was reprised by György Lukács in 1923. In the society of the spectacle, commodities rule the workers and consumers, instead of being ruled by them; in this way, individuals become passive subjects who contemplate the reified spectacle.
Keywords: Philosophy; Avant-garde; Crescendo; Material culture